A new Java tool for discrete simulation. (1st May 2009) - Drozdova, Martina; Zboril, Frantisek
The paper deals with a new tool for discrete system simulation called QS_PN_Simulation. This tool allows the easy creation of Queuing System (QS) models as Petri Net (PN) graphs. Simulation experiments with models can be done and the chosen statistical results of simulations can be obtained. The use of this system is demonstrated in the paper: the creation of a model of a chemical production system, simulation experiments with this model and the obtained results are presented here. The supposed extension of the proposed tool is then discussed in the conclusion of the paper.